Referral to an Electronic Screening and Brief Alcohol Intervention in Primary Health Care in Sweden: Impact of Staff Referral to the Computer - Preben Bendtsen; Diana Stark Ekman; AnneLie Johansson; Siw Carlfjord; Agneta Andersson; Matti Leijon; Kjell Johansson; Per Nilsen (International Journal of Telemedicine and Applications)
The aim of this paper was to evaluate whether primary health care staff's referral of patients to perform an electronic screening and brief intervention (e-SBI) for alcohol use had a greater impact on change in alcohol consumption after 3 month, compared to patients who performed the test on their own initiative. Staff-referred responders reported reduced weekly alcohol consumption with an average decrease of 8.4 grams. In contrast, self-referred responders reported an average increase in weekly alcohol consumption of 2.4 grams. Staff-referred responders reported a 49% reduction of average number of heavy episodic drinking (HED) occasions per month. The corresponding reduction for self-referred responders was 62%. The differences between staff- and self-referred patient groups in the number who moved from risky drinking to nonrisky drinking at the followup were not statistically significant. Our results indicate that standalone computers with touchscreens that provide e-SBIs for risky drinking have the same effect on drinking behaviour in both staff-referred patients and self-referred patients.